Religiosity and Career Commitment on Work Performance Among Teachers - Zaharuddin, Zaharuddin; Nur Auliya, Nabilla; Despiana, Dwi (Psikis : Jurnal Psikologi Islami, 2024)
This study examines the positive relationship between religiosity, work commitment, and work performance among teachers and academic staff at the Islamic Education Foundation. The results indicate that religiosity and commitment to work reinforce each other, leading to better work outcomes. With religiosity and career commitment contributing significantly to work performance (R² = 0.498), teachers with high levels of these attributes are more likely to improve their performance. Educational institutions are advised to integrate religious values into professional development programs through workshops, training, and seminars to enhance teacher performance. Using a quantitative research approach, this study collected data via questionnaires from 94 active teachers and academic staff, comprising 24 men and 70 women, residing in Muara Enim. Data analysis involved multiple linear regression and snowball sampling techniques. The study highlights the importance of religiosity in work performance, suggesting that fostering religious awareness and career commitment can significantly enhance staff performance. These findings underscore the need for professional development programs that emphasize religious values in the workplace, benefiting both individuals and organizations